Two new convenient syntheses of 14C‐squalene from turbinaric acid. (10th September 2018) - Philippe, Nicolas; Rivron, Luc; De Bruin, Béatrice; Schofield, Joseph; Roy, Sébastien
Abstract : Carbon‐14 labeled (6E, 10E, 14E, 18E)‐2, 6, 10, 15, 19, 23‐hexamethyltetracosa‐2, 6, 10, 14, 18, 22‐hexaene, also known as squalene, was synthesized as a tool for pharmacokinetic studies. Two simple and efficient labeling approaches were developed to give [2‐ 14 C]‐squalene and [3‐ 14 C]‐squalene from a halogenated precursor derived from turbinaric acid. They were obtained in 13.5% radiochemical yield in 6 steps and in 38% radiochemical yield in 3 steps respectively from carbon‐14 labeled potassium cyanide with a radiochemical purity higher than 98% in both cases. Abstract : [2‐ 14 C]‐squalene and [3‐ 14 C]‐squalene were synthesized using two efficient approaches from turbinaric acid. They were obtained in 13.5% radiochemical yield in 6 steps and in 38% radiochemical yield in 3 steps respectively from carbon‐14 labelled potassium cyanide with a radiochemical purity higher than 98% in both cases.